Total Quality Management and Organizational Performance : Mediated by Innovation at SMP Ar-Risalah Islamic Boarding School Padang City - Fahrezi, Tantowy Ahmad; Mesta, Hendri Andi (Universitas Negeri Padang, 2024)
This study set out to examine the link that exists between total quality management and organizational performance in the presence of innovation as a mediator or variable. The population of this study were all teachers and education personnel at the SMP Ar-Risalah Islamic Boarding School as many as 45 people. The number of samples used in the study was 45 people using the total sampling technique. This study employed causality research as its research strategy. With the aid of SmartPLS 4.0, the Structural Equational Model (SEM) is the data analysis method employed. The study's findings suggested that; (1) total quality management has an important and favorable impact on organizational performance; (2) organizational performance is positively and significantly impacted by innovation; (3) total quality management significantly and favorably influences innovation; (4) innovation isn’t able to act as a mediator in the link between total quality managememt and organizational performance.